Akibat Hukum Apabila Pekerja Outsourcing Tidak Mendapatkan Perlindungan Hukum - Haurissa, Yeheskel; Salmon, Hendrik; Pattipawae, Dezonda Rosiana (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Legal protection for outsourced workers or workers is very necessary considering that the position of workers or laborers is in a lower or weaker position. Protection of workers or laborers is intended to guarantee the fulfillment of workers' basic rights and guarantee equality of opportunity and non-discriminatory treatment on any basis to create prosperity for workers or laborers. The purpose of this research is to examine and analyze the legal consequences if outsourced workers do not receive legal protection. The research method used is normative juridical research, namely research in the field of law which aims to examine legal principles, legal rules and legal systems. The legal materials used are primary legal materials and secondary legal materials. The problem approaches used in this research are the statutory approach and the conceptual approach. The research results show that the weaknesses contained in providing protection to workers/laborers or outsourced workers who work with the PKWT system include, among others, weaknesses in the legal substance; Weaknesses related to employment agreements; Weaknesses of Companies Providing Outsourced Workers/Labor Services. Legal consequences if outsourced workers do not receive legal protection: 1) The flexibility of outsourcing can trigger the practice of modern slavery; 2) Decreasing long-term job security and the number of permanent workers; 3) Vulnerability of workers' guarantees and rights.